Hyperacute assessment of vertigo in suspected stroke - Morrow, Stacy; Koohi, Nehzat; Kaski, Diego (Frontiers in Stroke, 2023)
The management of patients with acute vertigo is most challenging in the hyperacute phase, both due to the complexity of vertigo as a symptom, the range of possible causes, and the lack of training in neuro-otology for non-specialists. Perhaps of greatest relevance is differentiating between peripheral (usually benign, e.g., inner ear) causes and central (potentially more sinister, e.g., stroke) causes. Several diagnostic algorithms have been introduced to help detect stroke in patients with acute vertigo. However, these algorithms have been validated in patients with an acute vestibular syndrome for whom symptoms have been present for a minimum of 24 hours. The most challenging period within the diagnostic process is the hyperacute phase that determines triage and treatment, but where none of the established algorithms have been validated. In this review, we specifically describe practical implementation considerations for evaluating patients with hyperacute vertigo, including the timing of diagnostic testing within the emergency department pathway, resource availability, and pitfalls associated with current practices.